2017
DOI: 10.1016/j.enbuild.2017.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Simple inlet devices and their influence on thermal stratification in a hot water storage tank

Abstract: • Stratification and hydrodynamics of a hot water tank during charging are studied. • A 3D-CFD model was used to supplement previous experimental analyses. • A high degree of correlation with experiments and versatility was achieved. • New inlet configurations and two inflow rates were simulated and compared. • The role of some inlet characteristics on stratification is clarified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Among the more recent numerical studies, Bouhal et al [9] performed 2D-CFD simulations to assess the thermal stratification in an HWST and the impact of flate plates position within a tank. Moncho-Esteve et al [10] implemented a 3D-CFD model to study the flow field and thermal stratification during charging. Once validated, the model was used to accomplish slight modifications of the inlet devices with the intention of optimizing system efficiency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the more recent numerical studies, Bouhal et al [9] performed 2D-CFD simulations to assess the thermal stratification in an HWST and the impact of flate plates position within a tank. Moncho-Esteve et al [10] implemented a 3D-CFD model to study the flow field and thermal stratification during charging. Once validated, the model was used to accomplish slight modifications of the inlet devices with the intention of optimizing system efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The study is completed with a comparison between the VTC method when using fewer measurement points and a numerical 3D-CFD approach, previously developed and validated in [10] with the same storage tank and experimental tests. Specifically, a comparison is made between the results obtained with the two methods when applied to the estimation of the instantaneous temperature profile.…”
Section: Introductionmentioning
confidence: 99%
“…In the aspect of tank thermal stratification during DHW discharge, Castell et al [6] studied the suitability of the most used dimensionless numbers for characterizing stratification in water tanks and found that Richardson number was the best number to define stratification in a water tank, while Mix number presented some problems and a bad behavior. As to the inlet effect, Moncho-Esteve et al [7] analyzed the influence of simple inlet devices on the thermal stratification of a cylindrical hot water storage tank by CFD techniques and reported that a sintered bronze conical diffuser could improve stratification compared to a conventional bronze elbow inlet.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Turbulence and mixing created by inlet flow affect considerably thermal stratification, for this reason a lot of researchers have investigated various inlet designs and their effect on stratification. A sintered bronze conical diffuser is considered to favor stratification for both low and high flows (García-Marí et al, 2013;Moncho-Esteve et al, 2017). Others suggest that a divergent conical tube diffuser creates better thermal stratification due to better diffusion of water (Alizadeh, 1999).…”
Section: Introductionmentioning
confidence: 99%